Unmet expectations: social inclusion and the interaction between social anxiety and ambiguous or positive feedback - Thériault, Rémi; Dion-Cliche, Flavie; Dandeneau, Stéphane (Frontiers in Psychology, 2023)
Introduction This study explores the impact of preferential inclusion on fulfilling basic needs following ambiguous or positive social feedback, considering the moderating effect of social anxiety. Methods Participants (N = 438) received either positive or ambiguous social feedback and engaged in a social participation or preferential social inclusion task. They completed measures of the fulfillment of their fundamental needs, social anxiety, and other personality traits. Results The results indicate that preferential social inclusion (Uberball condition) enhances the fulfillment of fundamental needs compared to social participation (Cyberball inclusion condition). Furthermore, receiving positive social feedback considerably strengthens the negative relationship between social anxiety and fundamental need fulfillment when followed by ordinary social participation relative to preferential social inclusion presumably because these individuals react more strongly to unmet expectations of extreme social acceptance. Discussion This research suggests that individuals with high social anxiety may not experience the usual benefits of social participation unless they experience extreme social inclusion.